Semantic space of adjectives for denoting emotions in german language - Makoviichuk, Liliana; Lekh, Olha (My University, 2024)
This paper presents a comprehensive study of the semantic field of "Emotions" in the German language. It has been estab- lished that the semantic field of "Emotions" consists of two main microfields: positive and negative emotions. A component anal- ysis of adjectives denoting emotions has been conducted to identify dominant semantic features and their distribution across the semantic fields. It has been found that adjectives for positive emotions are characterized by such semantic features as "joyful", "happy", "cheerful", while adjectives for negative emotions include features like "sad", "gloomy", and "lamentable". The analysis revealed that in German literary texts, negative emotionality is represented more broadly and vividly than positive emotionality. This indicates a literary tendency towards a deeper and more diverse portrayal of negative emotional states. At the same time, although positive emotions are less frequently expressed, they maintain their important role in depicting the emotional state of characters. This study expands the knowledge of the lexical system of the German lan- guage and contributes to a better understanding of the mechanisms of emotion expression in speech. Special attention in the study is given to the component analysis of adjectives denoting emotions. It has been clarified that adjectives for positive emotions include such semantic features as "happy", "joyful", "cheerful", reflecting a positive perception of events. Meanwhile, adjectives for negative emotions include features such as "sad", "gloomy", "lamentable", indicating negative emotional states. It has been established that in literary texts, negative emotions are expressed more frequently than positive ones, highlighting the depth and complexity of human experiences. The study ultimately concludes that the semantic field of "Emotions" in the German language represents a complex system of interrelated lexical units. The component analysis of adjectives allows for a more detailed examination of this field's structure and reveals the main tendencies in the usage of emotional lexemes. The findings of the study contribute to a better understanding of not only the lexical system of the German language but also the mechanisms of emotion expression in various linguistic contexts.
Keywords: Semantic field, adjectival lexeme, microfield, seme, component analysis.